Biochemical and microbiological investigations of subclinical mastitis in cows - Mehmet NİZAMLIOĞLU; Tevfik TEKELİ; Osman ERGANİŞ; Nuri BAŞPINAR (Eurasian Journal of Veterinary Sciences)
The aim of this study *was to investigate some 'biochemical and microbiological values for the early diagnosis of subclinical mastitis in healthy and mastitic cows.